Kidney Dyads: Caregiver Burden and Relationship Strain Among Partners of Dialysis and Transplant Patients - Van Pilsum Rasmussen, Sarah E. (Transplant Direct, 2020)
BACKGROUND. Caring for dialysis patients is difficult, and this burden often falls on a spouse or cohabiting partner (henceforth referred to as caregiver-partners). At the same time, these caregiver-partners often come forward as potential living kidney donors for their loved ones who are on dialysis (henceforth referred to as patient-partners). Caregiver-partners may experience tangible benefits to their well-being when their patient-partner undergoes transplantation, yet this is seldom formally considered when evaluating caregiver-partners as potential donors. METHODS. To quantify these potential benefits, we surveyed caregiver-partners of dialysis patients and kidney transplant (KT) recipients (N = 99) at KT evaluation or post-KT. Using validated tools, we assessed relationship satisfaction and caregiver burden before or after their patient-partner’s dialysis initiation and before or after their patient-partner’s KT. RESULTS. Caregiver-partners reported increases in specific measures of caregiver burden (P = 0.03) and stress (P = 0.01) and decreases in social life (P = 0.02) and sexual relations (P < 0.01) after their patient-partner initiated dialysis. However, after their patient-partner underwent KT, caregiver-partners reported improvements in specific measures of caregiver burden (P = 0.03), personal time (P < 0.01), social life (P = 0.01), stress (P = 0.02), sexual relations (P < 0.01), and overall quality of life (P = 0.03). These improvements were of sufficient impact that caregiver-partners reported similar levels of caregiver burden after their patient-partner’s KT as before their patient-partner initiated dialysis (P = 0.3). CONCLUSIONS. These benefits in caregiver burden and relationship quality support special consideration for spouses and partners in risk-assessment of potential kidney donors, particularly those with risk profiles slightly exceeding center thresholds.